ALTGÖZ KAPAĞI TÜMÖRLERİNDE TRIPIER FLEPLE ONARIM - AYDIN, Yağmur; GÜZEL, Zeki; TAŞ, Tamer; KUYUBAŞI, Selçuk; YILDIRIM, İbrahim (Cerrahpaşa Medical Journal, 2019)
Background.- The aim of the study was to evaluate the late results of lower eyelid defects, which were reconstructed by myocutaneus flaps prepared from upper eyelid and septal chondromucosal graft. Design.- 13 patients with lower eyelid defects due to neoplasm resection were reconstructed by myocutaneus flap prepared from upper eyelid and septal chondromucosal graft between 1989 and 1999. Results.- Five patients that lost 50% of lower eyelid were reconstructed by unipedicular myocutaneous flaps, while remaining 8 patients with defect of more than 50% of lower eyelid were reconstructed with bidepicular myocutaneous flaps. Patients were followed between 1 to 10 years. No complications were seen during early and late follow up periods. Conclusion.- Tripier flap is an alternative method to other procedures for lower eyelid reconstructions. It has lower complication rate and functionally and cosmetically beter results. Especially it must be the first choice of surgeon for horizontally oriented lower eyelid full thickness defects.